Analisis Yuridis Terhadap Tugas dan Wewenang Majelis Pengawas Notaris Setelah Diundangkannya Undang-Undang No. 2 Tahun 2014 Tentang Perubahan Atas Undang-Undang No. 30 Tahun 2004 Tentang Jabatan Notaris - Yandi Wijaya Silalahi (USU LAW JOURNAL, 2019)
Abstract. The enactment of Law No. 2/2014 on the Amendment to Law No. 30/2004 on Notary Position has caused changes in the authority of Notary Supervisory Council. This research aims to know, Firstly, how the duty and authority of the Notary Supervisory Council is before the imposition of Law No. 2/2014 compared to the one after it. Secondly, what impacts are brought by the revocation of the authority of the Notary Supervisory Council in relation to the approval given for the benefit of the trial process on Notary’s compliance with the Notary Supervisory Council. Thirdly, what obstacles are encountered by the Notary Supervisory Council in performing their duty and authority pursuant to Law No. 2/2014 on the Amendment to Law No. 30/2004 on Notary’s Position. This research employs normative juridical method and the data are collected through library study and field research while the data analysis is done qualitatively. This research was conducted by using normative juridical research method and data collection through literature study and field research and data analysis was done qualitatively. From the results of this study is expected to get a picture related to changes in the authority of the Notary Supervisory Board.   Keywords: Notary Supervisory Council, Supervision and Notary